36 Direct Measurement of Cardiac Compensation in Valvular Heart Disease. (6th June 2015) - Hothi, Sandeep; Tan, David; Schlosshan, Dominik; Tan, Lip Bun
Abstract : Purpose: The natural history of valvular heart disease (VHD) suggests that the heart initially adapts to compensate for valve lesions and thereby maintain physiological function. When these compensatory mechanisms become exhausted, cardiac decompensation commences. We tested the hypothesis that all VHD patients with normal exercise capacity are in the compensatory phase with no symptoms and normal cardiac reserve. Methods: Unselected consecutive male patients with VHD performed cardiopulmonary exercise (CPX) testing with non-invasive central haemodynamic measurements during symptom-limited treadmill exercise. Exercise capacity was represented by peak oxygen consumption (VO2max ) and cardiac pumping capability by peak exercise cardiac power output (CPOmax ). Data are given as mean±SD. Results: Of the entire VHD patient cohort (n = 215), 81.4% (n = 175) had VO2max which were within or above the reference range of healthy male sedentary controls (n = 101). This is shown in Figure 1A where individual patient VO2max is expressed as a percentage of the average VO2max of age- and sex-matched controls. These 175 patients with normal VO2max had a mean age of 63.1 ± 14.0 years, and consisted of 98 (56%) who were asymptomatic (NYHA class I) and 77 (44%) who were discordantly symptomatic in NYHA II+ (.001). As shown in Figure 1B, 117 patients (66.9%) had CPOmax within the normal range, of whom 80 (45.7%) were asymptomatic, but 37 (21.1%) were in NYHA II+ despite having normal VO2max and CPOmax (.001). Conversely, 58 (33.1%) had CPOmax below the normal range, and yet 18 (10.3%) of these were discordantly still in NYHA I (P < 0.001). These patients were classified asymptomatic by their responsible clinicians but our results revealed they had early, objective evidence of cardiac decompensation. Conclusions: This investigation demonstrates that it is now possible to directly and objectively measure whether patients are in the compensated or decompensated phases of VHD. There were discrepancies between subjective symptomatic statuses and objectively measured cardiac and physical functional statuses. The possibility to determine whether patients are in the compensatory phase or not, might help in the management of difficult VHD cases.